INTERCULTURAL EXPOSURE THROUGH ENGLISH FOR FOREIGN LANGUAGE COURSEBOOK A Closer Look at English in Mind Students Book 3 - Tirsana W. Kailola (Magister Scientiae, 2017)
As English serves as Lingua Franca in many parts of the world, cultural teaching and developing intercultural awareness have become important issues in EFL teaching. Therefore, cultural presentation and learning in English course book is one important issue to be investigated. This present study analyzes the presentation of culture and types of cultural exposure in a course book entitled English in Mind Students Book 3. The content analysis is based on the theory of Adaskou, et all (1990); Cortazzi & Jin (1999) and Xiao’s (2010), all of which posit that culture learning/teaching and the themes to accomplish this are important for contemporary ELT culture acquisition. The study finds that course book portrays culture mainly in the form of visual illustration. Subsequently, the source culture, the target culture and the international culture are found in unbalanced proportion where the target culture references are more dominant than the source culture and the international culture. There was a strong sense of a hierarchical representation of the inner circle world in which the British and the US cultures served as the supreme source. Investigating the result of cultural domain, small “c’ culture is highlighted over big ”C” culture. However, sixteen themes under big ”C” and small “c” are focused on the target culture. Cultural value and life style are the most frequent themes which appear in the course book.